Pengaruh Kredibilitas Green Advertising dan Sales promotion Starbucks terhadap Keputusan Pembelian : Survei pada Followers Instagram @starbucksindonesia - Alya Salsabilla; Aminah Swarnawati (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
Starbucks is one of the brands committed to sustainability by combining sales promotions with sustainability messages to attract the attention of environmentally conscious consumers as a marketing strategy. This study aims to determine the credibility of green advertising, determine sales promotions, determine purchasing decisions, measure the influence of green advertising credibility, measure the influence of sales promotions, measure the influence of green advertising and sales promotions credibility on purchasing decisions. The theories used in this study are the credibility of green advertising Verleye and De Ryuck (2023), sales promotions Kotler and Armstrong (2020), and purchasing decisions Kotler and Armstrong (2020). This study uses a quantitative approach with a survey method, and questionnaires are distributed as data collection instruments. The sample in this study was 126 respondents from Instagram followers @starbucksindonesia who were determined using the Slovin formula, then the sample was drawn using a simple random sampling technique. The results of this study indicate that respondents responded in agreement with the credibility of green advertising (X1), respondents responded in agreement with sales promotions (X2), respondents responded in agreement with purchasing decisions (Y), and the credibility of green advertising and sales promotions has an influence on purchasing decisions. This study shows that simultaneously the credibility of Starbucks' green advertising and sales promotions has a significant influence on purchasing decisions.